Oudheid als ambitie. - Enenkel, K. A. E., author.
1 online resource.
Keywords: This monograph studies the constructions of ‘impressive’ historical descent manufactured to create ‘national’, regional, or local antiquities in early modern Europe (1500-1700), especially the Netherlands. This was a period characterised by important political changes and therefore by an increased need for legitimation; a need which was met using historical claims. Literature, scholarship, art and architecture were pivotal media that were used to furnish evidence of the impressively old lineage of states, regions or families. These claims related not only to Classical antiquity (in the generally-known sense) but also to other periods that were regarded as periods of antiquity, such as the chivalric age. The authors of this volume analyse these intriguing early modern constructions of appropriate “antiquities” and investigate the ways in which they were applied in political, intellectual and artistic contexts in Europe, especially in the Northern Low Countries. This book is a revised and augmented translation of Oudheid als ambitie: De zoektocht naar een passend verleden, 1400–1700 (Nijmegen: Vantilt, 2017).